FORMULATION AND IN VITRO EVALUATION OF ORODISPERSIBLE TABLETS OF TENELIGLIPTIN - FARHEEN THABASSUM; PRAVEENA CHINTHALA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Teneligliptin is a newly advanced oral dipeptidyl peptidase 4 inhibitor used for the treatment of type 2 diabetes mellitus in adults alongside exercise and diet. In this study, teneligliptin orodispersible tablets (ODTs) were developed to improve solubility and bioavailability. Methods: In the present work, using various superdisintegrants such as croscarmellose sodium, sodium starch glycolate (SSG), and Crospovidone, a total of nine formulations of teneligliptin ODTs were developed by the direct compression method. All the developed formulations were subjected to in vitro characterization and studied for various physicochemical properties, drug release studies, and release kinetics. The physical stability study was conducted on the optimized formulation for 6 months. Results: All the developed formulations met the pharmacopoeial limits for weight variation, hardness, friability, and drug content. Among nine formulations, the F9 formulation showed the fastest disintegration time of 15 s and 99.12% of drug release within 15 min. Based on the wetting time, disintegration, and drug release studies, the F9 formulation was selected as the optimized formulation. Further, the F9 formulation was stable for 6 months. Conclusion: Teneligliptin ODTs were successfully prepared by the direct compression method using croscarmellose sodium, SSG, and crospovidone as super disintegrants. The optimized formulation F9 showed the highest drug release and was stable for 6 months.